A New TDR Multiplexing System for Reliable Electrical Conductivity and Soil Water Content Measurements. Issue 2 (2nd May 2013) - Weihermüller, L.; Huisman, J.A.; Hermes, N.; Pickel, S.; Vereecken, H.
Abstract : Time domain reflectometry (TDR) is a standard method to estimate soil water content and bulk soil electrical conductivity. In many applications, several TDR probes are installed in soil columns or field setups, and TDR measurements are acquired using a multiplexing system. Commercially available multiplexers share a common ground, which might lead to inaccurate TDR measurements when probes are installed close together or at sites with high electromagnetic noise. Therefore, a new eight‐channel differential multiplexer (50C81‐SDM) was developed that allows communication with standard TDR equipment. In a first step, the new multiplexer was tested to analyze channel noise and channel to channel variability for open reflection coefficients and travel times. The results indicate that there is no significant difference between the channels for both the open reflection coefficient and travel times. Second, the 50C81‐SDM multiplexer was tested using TDR probes installed in electrolyte solutions and a sand tank. In contrast to multiplexers with a common ground, they showed no interference of closely spaced TDR probes (spacing ranging from 5 to 95 cm). On the other hand, the SDMX50 multiplexer showed absolute differences in bulk electrical conductivities of >0.001 Sm −1 for high volumetric water contents and high bulk electrical conductivities. Measurements at a test site with high electromagnetic noise showed the applicability of the 50C81‐SDM multiplexer in such environments, but only if the entire TDR setup was disconnected from the permanent power supply.